Secreted stromal protein ISLR promotes intestinal regeneration by suppressing epithelial Hippo signaling. (4th March 2020) - Xu, Jiuzhi; Tang, Yang; Sheng, Xiaole; Tian, Yuhua; Deng, Min; Du, Sujuan; Lv, Cong; Li, Guili; Pan, Yuwei; Song, Yongli; Lou, Pengbo; Luo, Yongting; et al.
Abstract: The Hippo–YAP signaling pathway plays an essential role in epithelial cells during intestinal regeneration and tumorigenesis. However, the molecular mechanism linking stromal signals to YAP‐mediated intestinal regeneration and tumorigenesis is poorly defined. Here, we report a stroma–epithelium ISLR–YAP signaling axis essential for stromal cells to modulate epithelial cell growth during intestinal regeneration and tumorigenesis. Specifically, upon inflammation and in cancer, an oncogenic transcription factor ETS1 in stromal cells induces expression of a secreted protein ISLR that can inhibit Hippo signaling and activate YAP in epithelial cells. Deletion of Islr in stromal cells in mice markedly impaired intestinal regeneration and suppressed tumorigenesis in the colon. Moreover, the expression of stromal cell‐specific ISLR and ETS1 significantly increased in inflamed mucosa of human IBD patients and in human colorectal adenocarcinoma, accounting for the epithelial YAP hyperactivation. Collectively, our findings provide new insights into the signaling crosstalk between stroma and epithelium during tissue regeneration and tumorigenesis. Synopsis: YAP activation in the intestinal epithelium is linked to intestinal regeneration and tumorigenesis. Here, the mesenchyme‐derived extracellular protein ISLR is shown to mediate stroma‐epithelium crosstalk in the intestine to activate YAP both during regeneration and cancer formation. Stromal ISLR levels are increased in inflamed intestinal mucosa of human patients with inflammatory bowel disease and colorectal adenocarcinoma. Transcription factor ETS1 directly induces ISLR expression in stromal cells. In mice, deletion of Islr in stromal cells impairs intestinal regeneration and suppresses tumorigenesis in the colon. Stromal ISLR suppresses Hippo signaling in epithelial cells. Context‐dependent YAP activation via ISLR promotes either intestinal regeneration or tumorigenesis. Abstract : Disease‐associated or regenerative YAP activation in the intestinal epithelium is triggered by the mesenchyme‐derived extracellular protein ISLR.